The Cambridge constitutional history of the United Kingdom - Cane, Peter 1950-; Kumarasingham, Harshan 1979- (Cambridge University Press, 2023)
"This ground-breaking volume brings together the methods and insights of historians, lawyers and students of politics to give readers an appreciation not only of the historical development, legal nature and political importance of the constitution, but also of its general relevance to all aspects of human social life"--